Synergistic potential of co-millinged edible argan oil (Argania spinosa L.) and oregano leaves (Origanum vulgare L.) in food applications - Samira Oubannin; Abderrahim Asbbane; Otmane Hallouch; Angelo Maria Giuffrè; El Hassan Sakar; Said Gharby (Future Foods)
By including oregano (Origanum vulgare L.) leaves (OL) during the extraction process, the nutraceutical benefits of argan oil (AO) can be significantly increased. Thanks to the employed technique (enrichment through extraction), without resorting to organic solvents. The current work aimed at developing of a green enrichment of argan oil with 2 and 5 % of OL. The purpose of this research was to evaluate the effectiveness of adding OL and its impact on AO oxidative stability under accelerated oxidation for four months. AO physicochemical characterization consisted in measuring quality indices, total phenolic contents, antioxidant activity, pigments, and sensory analysis throughout the storage period. In general, AO samples containing OL exhibited increased phenolic, chlorophylls, and carotenoid contents and lower peroxide and p-anisidine values. AO shelf-life was extended thanks to OL, which slowed down the process of lipid complete oxidation. From a sensory standpoint, a rancid taste was found in the unenriched AO, while the taste and color of oregano were more intense in the AOs supplemented with OL at 5 %. This innovative approach boost AO value in various industries and exemplifies the endless possibilities that emerge when we explore the synergy between different natural elements.